THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND PHYSICAL ACTIVITY WITH THE INCIDENCE OF PRIMARY DYSMENORRHEA IN SMAN 1 NORTH TAMBUN STUDENTS IN 2023 - Alliffiyola Lani Putri; Nurfadhilah; Dadang Herdiansyah; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
The symptoms of a condition called dysmenorrhea include severe, painful cramps and lower abdominal cramping sensations. Primary dysmenorrhea is 72.89% common in Indonesia, but dysmenorrhea prevalence varies from 45% to 95% in women of reproductive age. It has been determined through research at SMAN 1 Tambun Utara that dysmenorrhea affects up to 65% of students with abnormal nutritional status and 39.3% of students with normal nutritional status. The purpose of this study is to ascertain how the occurrence of primary dysmenorrhea in SMAN 1 Tambun Utara students is related to their nutritional status and level of physical activity. A cross-sectional study design and quantitative analysis techniques were used in the investigation. 95 students made up the sample, which was chosen using the stratified random sampling technique. Two phases of data analysis—univariate and bivariate analysis—were used. The kai squared test with α = 0.05 was used to examine the data. The findings demonstrated a correlation between the occurrence of primary dysmenorrhea and both physical activity (p-value = 0.000) and nutritional status (p-value = 0.000). The findings of this study suggest a relationship between the occurrence of primary dysmenorrhea and physical activity and nutritional status. A balanced and nutritious diet, regular weight checks, regular exercise, and abstaining from unhealthy behaviors that can lead to primary dysmenorrhea are all healthy lifestyle choices that students aspire to.